An analysis of employee retention : a study of selected local municipalities in the Sarah Baartman District Municipality - Maholo, Lisa (Rhodes University, Faculty of Commerce, Department of Management)
The success of municipalities largely depends on the quality (skills, knowledge and experience) of individuals employed at those institutions. As key role players in the delivery of services, municipalities struggle to retain a high calibre of employees who essentially form the backbone of the public sector due to their skills, knowledge and experiences. There is a need for municipalities to create and foster an environment that encourages existing employees to remain employed. This study adopted an interpretivist research paradigm, given the study's primary aim of gaining an in-depth understanding of employee retention as experienced by employees in the selected municipalities, together with the key influencing factors of employee retention. The qualitative research approach used a case study methodology within the Sarah Baartman District Municipality, with two category B3 and B4 municipalities selected for the study. The retention factors framework for existing employees by Munsamy and Bosch-Venter (2009) was used as the supporting theoretical structure. Respondents were selected through purposive sampling, and 16 in-depth semi-structured interviews were used to collect qualitative data. Through various content analysis techniques employed, this study identified seven employee retention factors (affiliation, career, work content, direct financial factors, external forces, work"“life balance and indirect financial factors) with their associated themes. Affiliation, career and work content were identified as the three key factors which influence employee retention. Management style (relationship and interaction between employees and manager), organisational commitment and work environment were the main themes giving meaning to the affiliation factor. Training, personal growth and advancement emerged as themes related to the career factor. The work content factor was defined in terms of meaningfulness, challenges and autonomy themes. Direct and indirect financial factors, external forces, and work"“life balance also emerged as factors that play a role in the retention of employees within a municipal context. Base salary and incentives were the associated themes underlying the direct financial factor. However, base salary has short-term effects on retention. Political climate and organisational reputation, municipal category and organisational structure were interrelated external forces. Flexible work arrangements, access to family, and childcare facilities give meaning to the work"“life balance, while the only indirect financial factor to arise was benefits. Although some of the retention factors are clearly more influential than others, key employees attach most importance to a combination of employee retention factors that cater to their holistic needs and desires and generational differences. Therefore, the recommendations need to be implemented simultaneously. Having managers who engage employees in decisions-making and offer guidance and support, together with work environments where the physical and behavioural aspects are attended to, encourages employees to feel valued and appreciated. Municipalities should effectively communicate their mandate of ensuring adequate service delivery, which will allow employees to align their personal values to municipal objectives. Offering on-the-job training, access to career developmental programmes, evaluating job characteristics to include challenging and stimulating work and additional incentives as financial support will foster a conducive working environment for employees. Overall, municipalities face unique challenges depending on a variety of external elements such as political influence and climate. They operate in a challenging environment where they are also accountable to the community. Ultimately, municipalities must create and develop ways to acknowledge, develop and retain key employees in order to adequately deliver services.
Keywords: Municipal government -- South Africa -- Eastern Cape; Employee retention -- South Africa -- Eastern Cape; Labor turnover -- South Africa -- Eastern Cape; Municipal officials and employees -- Job satisfaction; Career development -- South Africa -- Eastern Cape; Personnel management -- South Africa -- Eastern Cape; Municipal officials and employees -- Salaries, etc. -- South Africa -- Eastern Cape; Affiliation (Psychology)